(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Lathridius anthracinus biology was studied on chocolate also experimentally inoculated with different fungi species isolated from food products. L. anthracinus needs a particularly humid environment, without too high temperatures: at 21°C and with 80% R.H., the largest increase of population was noted. It was observed that, in absence of mycelium, insect development is prevented. Otherwise the most favourable conditions of development happened in presence of some species of moulds; Penicillium stoloniferum and Aspergillus fumigatus proved particularly suitable. Nevertheless the period of time necessary to get the emerging of adults-moulds being equal is the longest one in the case of rearing carried out in presence of agar-mould. The shortest period of development in the most favourable conditions happened on chocolate moulded with P. stoloniferum (23,6 days), while the longest one was on Aspergillus flavus bred on agar-malt (30,2 days).